Internationalization in vocational education and training : transnational perspectives - Tran, Ly thi [Herausgeber]; Dempsey, Kate [Herausgeber] (Springer, 2017)
"This edited book addresses a range of aspects of internationalization in vocational education and training (VET) in different countries. It considers the impact of internationalization and student mobility on VET at the sectoral, institutional and individual levels as the sector emerges as a key tool for social and structural change in developing nations and as a flexible and entrepreneurial means of growth in developed nations. The book explores not only the effects of the neo-liberal market principle underpinning VET practices and reforms, but importantly considers internationalization as a powerful force for change in vocational education and training. As the first volume in the world that examines internationalization practices in VET, the book provides VET and international education policymakers, practitioners, researchers and educators with both conceptual knowledge and practical insights into the implementation of internationalization in VET." (Publisher, BIBB-Doku)

Part I: Internationalization and Its Impact on VET; Part II: VET Transfer and Appropriation; Part III: Extending the VET Boundaries.
Keywords: I 1 Internationale Berufsbildung; P 3.2.3 Lehrer; I 2.3.2 Nordamerika; I 2.3.5 Australien, Ozeanien; I 2.3.4 Asien; Berufsbildung; Internationalisierung; Berufsschullehrer; Lehrerbildung; Berufsbildungspolitik; USA; Australien; Laos; Kuwait; Vietnam; Korea; Niederlande; China; Bundesrepublik Deutschland